(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the effect of providing shade to Girolando cows on milk yield and composition, physiological parameters, hemogram and blood pH. Two treatments were used: paddocks with and without shade. Animals were alternately kept in each treatment for a period of 15 days for three times. Milk production was recorded and measurements were taken for rectal temperature, skin surface and udder surface temperatures. A total of 24 blood samples were collected form each cow during the experimental procedure. This was done to compare the mean milk yield and chemical composition as well as physiological and blood parameters. The t-test was applied at 5% significance level. Milk urea was higher when the animals were kept in a shaded area. The morning recording for blood erythrocyte counts hematocrit, milk urea, rectal temperature, skin surface and udder surface temperatures showed interaction with respect to temperature ranges whereas the udder temperature in the afternoon showed a similar response. Girolando cows with 3/4 Holland + 1/4 Gyr and 7/8 Holland + 1/8 Gyr blood levels present an ability to adapt to the environment, and there was no effect of shading on milk yield and composition, physiological and blood parameters evaluated.